The sulfolipid sulfoquinovosyldiacylglycerol is not required for photosynthetic electron transport in Rhodobacter sphaeroides but enhances growth under phosphate limitation. - Benning, C (1993)
All photosynthetic organisms, with the exception of several species of photosynthetic bacteria, are thought to contain the sulfolipid 6-sulfo-alpha-D-quinovosyldiacylglycerol. The association of this lipid with photosynthetic membranes has led to the assumption that it plays some role in photosynthesis. Stable null mutants of the photosynthetic bacterium Rhodobacter sphaeroides completely lacking sulfolipid were obtained by disruption of the sqdB gene. The ratios of the various components of the photosynthetic electron transport chain, as well as the electron transfer rates during cyclic electron transport, were not altered in the mutants, when grown under optimal conditions. Growth rates of wild type and mutants were identical under a variety of growth conditions, with the exception of phosphate limitation, which resulted in reduced growth of the mutants. Phosphate limitation of the wild type caused a significant reduction in the amount of all phospholipids and an increased amount of sulfolipid. By contrast, the sulfolipid-deficient mutant had reduced levels of phosphatidylcholine and phosphatidylethanolamine but maintained a normal level of phosphatidylglycerol. In addition, two unidentified lipids lacking phosphorus accumulated in the membranes of both wild-type and mutant strains under phosphate limitation. We conclude that sulfolipid plays no significant unique role in photoheterotrophic growth or photosynthetic electron transport in R. sphaeroides but may function as a surrogate for phospholipids, particularly phosphatidylglycerol, under phosphate-limiting conditions.